Urgensi dan Efektifitas Sanksi Administrasi dalam Pengelolaan Limbah Bahan Berbahaya dan Beracun - Siti Ruhama Mardhatillah (Fakultas Hukum Universitas Islam Indonesia, 2016)
The implementation of administrative sanctions in Government Regulation No. 101 of 2014 on the Management of Hazardous and Toxic Waste (B3) has emerged a polemic in the form of inconsistency in the sanction enforcement under Act No. 32 of 2009 on the Protection and Management of the Environment (Law PPLH). Under the provisions concerning with the management of B3 waste as regulated in the Act of PPLH, criminal sanction is enforced as premium-remedium without any first enforcement of administrative sanctions. This study observed two issues: first, the urgency and the strategy of sharpening the existence of the administrative sanctions in the Regulation No. 101 of 2014 of the Law No. 32 of 2009. Second, it concerns with the effectiveness of the administrative sanctions in the management and supervision of B3 waste. This is a normative juridical law research. The study concluded that: first, although based on the law of PPLH criminal law is enforced in medium premium, but the role and presence of the administrative sanctions in the B3 waste management is necessary especially to develop any preventive measures against environmental pollution caused by the B3 waste. Second, although the Act of PPLH has applied the criminal sanctions in premium remedium, but the implementation of administrative sanctions is more effective and provides a protection against the threat of environmental pollution from waste B3.